Concerning reconnection‐induction balance at the magnetopause of Mercury. Issue 4 (6th April 2016) - Heyner, Daniel; Nabert, Christian; Liebert, Evelyn; Glassmeier, Karl‐Heinz
Abstract: Mercury's weak internal dipole field is subject to an intense solar wind; and thus, only a small magnetospheric cavity is created. The location of the outer boundary, the magnetopause, is mainly controlled by a pressure balance between the solar wind pressure outside and magnetic pressure inside, but during times of intense dayside reconnection the standoff distance may be reduced due to erosion. For the Hermean magnetosphere, different erosion mechanisms such as direct flux transport, neutral current sheet enhancement, field‐aligned currents, and interplanetary magnetic field penetration are compared. As any of these erosion mechanisms change the external field experienced by the planet, currents are induced within the electrically conductive planetary interior. Secondary magnetic fields from these induced currents counteract their source by temporarily increasing the planetary magnetic moment. The amplitude of this compensation depends on the interior electrical conductivity structure. Using a magnetospheric model, that is based on in situ MErcury Surface, Space ENvironment, GEochemistry, and Ranging data, as well as a simple conductivity model for the planetary interior, we give an estimate of the induced magnetic field range possible for various internal conductivity structures and external forcings. Considering the planetary response to the magnetospheric field changes opens a possibility to probe the planetary interior—a method especially suited for the upcoming BepiColombo mission to Mercury. Key Points: There are several potential magnetopause erosion mechanisms at Mercury The magnetotail enhancement is one of the main magnetopause erosion mechanism at Mercury Induction in the Hermean planetary interior may compensate for at least 15% of the erosion